The world of subjects in "Nazm Ul-Javahir" by Alisher Navai - Shirinova, Mexrigiyo (FILOLOGIYA UFQLARI JURNALI, 2024)
"Nazm ul-Javahir" is a work of Alisher Navoi’s poems. The wise words of Caliph Ali ibn Abu Talib were used as a basis for the poems in it. This article compares the sayings of Grace Ali and the poems of Alisher Navoi. Alisher Navoi’s artistic interpretation and creative development of the topics presented in the wisdom during the analysis are studied. The expressions of such topics as modesty, courage, forgiveness, patience, justice, gentleness, generosity, kindness, faithfulness to a covenant, and loyalty to a friend are analyzed in wisdoms and poems. Keywords: wisdom, poem, theme, idea, faith, loyalty, modesty, friendship, justice, diligence.